2020
DOI: 10.1186/s12884-020-02917-9
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity associated with gestacional and neonatal outcomes: a systematic review

Abstract: Background: Food insecurity (FI) occurs when people lack secure access to sufficient amounts of safe and nutritious food. FI has been associated with negative effects on human health, including during the prenatal and neonatal periods. The objective of this study is to evaluate the consequences of FI for pregnant women's and newborns' health. Methods: A literature search was performed with three independent researchers based on the PRISMA guidelines; the search covered the period of November 2008 to July 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…Food insecurity can have a negative impact on a range of health outcomes which are more pronounced in some population groups. Pregnant and postpartum women are especially vulnerable to the negative impacts of food insecurity, as they have increased nutritional requirements during pregnancy to meet the needs of the growing foetus [ 3 ], while after pregnancy they may have additional nutritional requirements for breastfeeding [ 4 ]. Research suggests that the dietary intakes of pregnant women often do not meet nutritional guidelines [ 5 •], and while some studies have explored the role of nutritional counselling [ 6 ], pregnant women may need more assistance in meeting their nutritional needs at this time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity can have a negative impact on a range of health outcomes which are more pronounced in some population groups. Pregnant and postpartum women are especially vulnerable to the negative impacts of food insecurity, as they have increased nutritional requirements during pregnancy to meet the needs of the growing foetus [ 3 ], while after pregnancy they may have additional nutritional requirements for breastfeeding [ 4 ]. Research suggests that the dietary intakes of pregnant women often do not meet nutritional guidelines [ 5 •], and while some studies have explored the role of nutritional counselling [ 6 ], pregnant women may need more assistance in meeting their nutritional needs at this time.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy can be a physically and mentally demanding time where food insecurity can exacerbate stress [ 3 ]. Many studies have found an association with food insecurity, and reduced quality of life and psychosocial outcomes such as increased depression and anxiety [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal antenatal nutrition promotes best health outcomes for the mother and baby (Procter & Campbell, 2014 ), however, pregnant women experiencing FI may be less able to access healthy foods. FI during pregnancy is associated with adverse outcomes such as excessive gestational weight gain, gestational diabetes, maternal anaemia, preterm birth, and birth defects (Augusto et al, 2020 ). Some of these obstetric complications are linked with longer term poor health outcomes for the offspring, such as diabetes and cardiovascular disease (Carolan-Olah et al, 2015 ; Luu et al, 2016 ), highlighting the potentially dire intergenerational impacts of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women who are food insecure frequently have poor diet quality and sub-optimal nutritional intake during pregnancy, leading to negative maternal and child health outcomes [ 3 , 4 ]. When compared to women who are food secure, women who are food insecure during pregnancy are at a higher risk of gestational diabetes [ 5 ], low birth weight [ 6 , 7 ], maternal stress [ 4 , 8 ], excess maternal weight gain [ 5 ], birth defects [ 9 ], premature birth, and struggle to breastfeed [ 10 , 11 ]. The impacts of food insecurity, and as a result inadequate nutrition, during pregnancy can be both significant and long term for mother and child, leading to challenges with child growth and development [ 4 , 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity and hunger during pregnancy have significant implications for the health of the mother and baby. Pregnant women who are food insecure frequently have poor diet quality and sub-optimal nutritional intake during pregnancy, leading to negative maternal and child health outcomes [3,4]. When compared to women who are food secure, women who are food insecure during pregnancy are at a higher risk of gestational diabetes [5], low birth weight [6,7], maternal stress [4,8], excess maternal weight gain [5], birth defects [9], premature birth, and struggle to breastfeed [10,11].…”
Section: Introductionmentioning
confidence: 99%